Frisks in Brazilian Law: a tool of criminal investigation or preventive policing? - Gisela Aguiar Wanderley (Revista Brasileira de Direito Processual Penal)
Brazilian policemen perform frisks (patdowns) routinely, which are comprehended as part of urban preventive policing. The high number of frisks daily performed is justified by its alleged importance to control crime and make police visible. Nevertheless, by examining legislation and legal studies, this paper aims to clarify that this way of practicing frisks in a preventive manner is illegal and relates to the lacking legal studies on the topic. It is stressed that frisks are legally regulated as a procedure of obtaining criminal evidence, which is conditioned to founded suspicion of possession of forbidden weapon or other objects or papers that constitute corpus delicti. Also, frisks may be performed in face of imminent danger, under justification defenses (necessity, self-defense or defense of others). Anyhow, frisks may not be performed as a routine procedure of criminal general prevention.